Imprint of a dissolved cobalt basaltic source on the Kerguelen Plateau - Bown, J.; Boye, M.; Laan, P.; Bowie, A. R.; Park, Y. -H.; Jeandel, C.; Nelson, D. M. (HAL CCSD, 2012)
International audience Processes of cobalt (Co) entrainment from shelf sediments over the Kerguelen Plateau were studied during the KEOPS (Kerguelen Ocean Plateau compared Study) in order to explain the exceptionally high dissolved cobalt concentrations that have been measured in the surface waters above the Kerguelen Plateau, and in intermediate and deep waters above its eastern slope. Lateral advection and dissolution of Co contained in basalt sediments around Heard Island, a main source of lithogenic Co in the study area, were shown to imprint the process of surface enrichment over the plateau. Dissolved Co enrichment was strongest at the intercept of the eastern slope with intermediate and deep waters, probably due to more efficient mobilisation of the sediments in the slope current, in addition to advection of Co-enriched and low-oxygenated ocean water masses. In surface waters, the strong sedimentary Co inputs were estimated to be much higher than biological Co uptake in phytoplankton blooms, underlining the potential use of dissolved cobalt as tracer of the natural iron fertilization above the Kerguelen Plateau. Based on a simple steady-state balance equation of the external input of dissolved iron over the plateau, the fertilization of iron inferred by using dissolved Co as a tracer of basalt sources is estimated to be 28 × 10 2 ± 21 × 10 2 t yr -1 in surface waters of the Kerguelen Plateau. This estimate is consistent with preceding ones (Zhang et al., 2008; Chever et al., 2010), and the calculated iron supply matches with the phytoplankton demand (Sarthou et al., 2008).